OPTIMASI PENENTUAN RUTE DISTRIBUSI BERAS KOMERSIAL BULOG MENGGUNAKAN METODE BRANCH AND BOUND DENGAN BANTUAN SOFTWARE LINGO - Dhian Herdhiansyah; Asmila Yunissa; Weka Gusmiarty; Asriani Asriani (AGROINTEK, 2023)
The purpose of this study was to optimize the distribution route of commercial rice for general logistics companies in Kendari City using the branch and bound method with the help of lingo software. This research was conducted at the Perum Bulog, Southeast Sulawesi Regional Office. Determination of the location of the research is done intentionally (purposive sampling) which considers that Perum Bulog in Kendari has regular customers, distributes its products, and requires optimization of route determination to optimize distribution costs. Variables in this study: (a) location and several customer requests; (b) Bulog's DC location and capacity; (c) the number and capacity of vehicles for the distribution of Bulog's commercial rice; and (d) the distance between Bulog's DC and customers and the distance between Bulog's commercial rice customers using Google Maps in the form of secondary data. Data analysis in research uses: (a) nearest neighbor method, done by starting from the Distribution Center Warehouse/DC Bulog Sultra as the starting point of distribution and then looking for customer points in Kendari City; (and (b) the branch and bound method assisted by the syntax script of the Lingo program. The study results show that the optimal route that can be used in the distribution of Bulog's commercial rice in Kendari City is from DC in Mandonga to all customers in various regions in Kendari City. Thenreturned to DC in Mandonga, where this route experienced a decrease in vehicle mileage from 424.83km to 349.59km. The branch and bound (BnB) method showed that it  optimize distribution routes so that the distance traveled by vehicles on each route cluster is reduced.